Intervening in the Media's Influence on Stereotypes of Race and Ethnicity: The Role of Media Literacy Education. (March 2015) - Scharrer, Erica; Ramasubramanian, Srividya; Mastro, Dana; Tukachinsky, Riva
<x xml:space="preserve">Abstract</x> This article provides a review of the research record on the potential for media literacy education to intervene in the media's influence on racial and ethnic stereotypes, and explores the theoretical concepts that underlie these efforts. It situates media literacy theory and practice within particular emphases in the field and synthesizes qualitative and quantitative studies. Quantitative research on the effect of media literacy training and mediated counterstereotypes on reducing racial/ethnic prejudice is described. In addition, we report qualitative data from an ongoing study of early adolescents who took part in a media literacy curriculum on stereotypes. The research record reveals that although the topic is severely understudied, media literacy education holds great promise for its ability to shape media‐related knowledge, attitudes, and behaviors and encourage an active and critical stance toward media.